A simple polypropylene fiber membrane embedded with clean La(OH)3 nanoparticles for highly efficient phosphate anions removal. Issue 5 (October 2022) - Zeng, Yanbo; Chang, Fengqin; Hu, Guangzhi; Zhang, Yang; Li, Donglin; Li, Hui; Wågberg, Thomas; Zhang, Hucai
Abstract: Lanthanide materials are attracting increasing attention owing to their ability to strongly bind with phosphorus (P). In this paper, a novel method of producing clean lanthanum nano-aerosols by spark ablation is proposed, the particles are uniformly deposited on a cheap and readily available Polypropylene(PP) fiber membrane in a special gas environment, and combined with water (solvent) for hydrothermal synthesis of the new material, PP-La. Material characterization confirmed that the formation of La(OH)3 nanoparticles and ligand exchange plays an important role in the phosphorus adsorption process, extended X-ray absorption spectroscopy demonstrated that phosphate was bound to the lanthanum site. The adsorption capacity of PP-La for phosphate is 188.6 mg P/g La, and the cost index (capacity/synthesis cost) is 132.54 mg P/USD. In addition, unlike most sorbents, PP-La has the advantage of being easily separated from water. This synthesis method is green and simple, the lanthanum is not toxic, the Polypropylene fiber membrane is cheap and has better mechanical strength, and the application prospect is very broad. Our results provide a new strategy for the development of efficient adsorbents and the treatment of eutrophication by selective adsorption of phosphate in lakes, reservoirs, rivers, and other water bodies. Graphical Abstract: The maximum phosphate adsorption capacity of La(OH)3 - Polypropylene synthesized by spark ablation attained 188.6 mg/g. ga1 Highlights: A new adsorbent synthesized by using spark ablation to generate lanthanum nano-aerosols embedded polypropylene fiber membrane. The maximum phosphate adsorption capacity attained 188.6 mg/g. Physical synthesis has great advantages in terms of environmental friendliness. The membrane has low cost, easily separated from wastewater, and have potential for scale production and recycling.